Realization of a Carrier-Based Unbalanced Output Space Vector PWM Strategy Using Analogue and Digital Techniques for Three-Leg Voltage Source Inverter Fed Two-Phase Induction Motors - Chakrapong Charumit; Vijit Kinnares (My University, 2009)
This paper proposes the realization of a carrier-based space vector pulsewidth modulation (SVPWM) method using analogue and digital techniques. This PWM method provides unbalanced phase outputs for a two-phase three-leg voltage source inverter (VSI). The principle is fully described. The proposed space vector equivalent phase leg reference voltages are derived from conventional ones. With the proposed SVPWM method, the amplitude of the unbalanced phase voltages can be easily controlled as required whilst the phase difference angle is kept at 90 degrees. This characteristic is suitable for a control method of an asymmetrical type two-phase induction motor. The validity of the proposed method is verified by both calculated and experimental results under a variation of PWM parameters with resistive-inductive and motor loads in terms of space vector equivalent reference waveforms, current waveforms and space vector trajectories and so on.
Keywords: Realization (probability); Three-phase; Multilevel Inverters and Converters